Total nucleated cells from bone marrow as an adjuvant treatment in a patient with third-degree burn - Samantha P. Peña-Lozano; Sandra A. Sánchez-García; Ileana Y. Velasco-Ruiz; Antonio I. Valencia-Alcocer; Jorge T. Palacios-Zertuche; Consuelo Mancías-Guerra (Elsevier, 2021)
Introduction: Third-degree burns are known to affect the epidermis, dermis, hypodermis and adjacent structures, causing damage to the dermal matrix. To date, the gold standard treatment is autologous skin grafting. However, its effectiveness is limited owing to its availability and cost. Depending on the severity of the wound, the maturation of the graft can take several weeks and the tcosmetic results are often unsatisfactory. Given the need to develop new therapies to improve the management and quality of life of patients, cell therapy has become a promising alternative. Objective: To describe the evolution of non-grafted third-degree burns after subcutaneous application of autologous bone marrow (BM) total nucleated cells (TNCs). Case report: We present the case of a 52-year-old male patient with a third-degree scald on the external surface of the left foot. Nine days after the burn, 2 ml of autologous BM TNCs were applied subcutaneously around the wound. An autologous skin graft was not performed; therefore, healing was by second intention. The patient had good clinical evolution without any keloid scars or complications. Conclusion: Although current treatments for third-degree burns still have limitations, recent studies have shown the effectiveness of stem cells in these types of burns by allowing accelerated healing. However, further studies are required to demonstrate their efficacy and safety.